The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22020897
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Underlying Hypertrophic Scarring Following Burns Involve Specific Deregulations at All Wound Healing Stages (Inflammation, Proliferation and Maturation)

Abstract: Excessive connective tissue accumulation, a hallmark of hypertrophic scaring, results in progressive deterioration of the structure and function of organs. It can also be seen during tumor growth and other fibroproliferative disorders. These processes result from a wide spectrum of cross-talks between mesenchymal, epithelial and inflammatory/immune cells that have not yet been fully understood. In the present review, we aimed to describe the molecular features of fibroblasts and their interactions with immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 185 publications
0
43
0
5
Order By: Relevance
“…It is conceivable that the ILK/Akt pathway may regulate proliferation and survival of various types of abnormal fibroblasts and may be promising for prevention and treatment of fibrosis. Abnormal activation of fibroblasts in wounds has been reported to lead to the occurrence of pathological repair [ 44 , 45 ]. This perspective is supported by our data, as we found that compared with normal airway fibroblasts, the ILK/Akt pathway was abnormally activated in PHAGF, leading to stronger proliferative activity and anti-apoptotic ability, and β-elemene suppressed the viability of PHAGF by attenuating its ILK/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the ILK/Akt pathway may regulate proliferation and survival of various types of abnormal fibroblasts and may be promising for prevention and treatment of fibrosis. Abnormal activation of fibroblasts in wounds has been reported to lead to the occurrence of pathological repair [ 44 , 45 ]. This perspective is supported by our data, as we found that compared with normal airway fibroblasts, the ILK/Akt pathway was abnormally activated in PHAGF, leading to stronger proliferative activity and anti-apoptotic ability, and β-elemene suppressed the viability of PHAGF by attenuating its ILK/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this microenvironment represents a highly dynamic system. As cryotherapy represents the acute phase of wounding, its "healing" is associated with time-limited activation of immune system in order to remove tissue debris and minimize risk of infection [70]. This also establishes a new immune equilibrium and changes the tumour promoting setting of the cancer-associated microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of wound repair, angiogenesis is essential for the delivery of oxygen and nutrients to the newly developed tissue. Angiogenesis is comprised of consecutive actions including migration and proliferation of endothelial cells orchestrated by growth factors, oxygen levels, and proteases [2]. Recently, it was revealed that genistein can impact the growth and budding of endothelial cells, the formation of new capillaries, and some of the signaling pathways connected to angiogenesis [78] also via alteration of vascular endothelial growth factor (VEGF).…”
Section: Angiogeneismentioning
confidence: 99%
“…Wound healing is a dynamic event running in four basic phases, i.e., hemostasis, inflammation, proliferation, and maturation/remodeling, which overlap with each other in a consecutive manner restoring the disrupted integrity of tissues/organs. Immediately following blood clotting inflammatory/immune cells enter the injury site to eliminate pathogens and remove necrotic tissue [2]. Fibroblasts located in the granulation tissue excrete and remodel extracellular matrix (ECM) proteins, whereas differentiated myofibroblasts contract the wound [3].…”
Section: Introductionmentioning
confidence: 99%